Modeling of Inverse Kinematic Analysis of Open-Source Medical Assist Robot Arm by Python - Gül, Ahmet (My University, 2021)
Today, the epidemic diseases such as COVID-19 spreads very fast in the globalizing world and lethal effects on human health have had a noticeable effect on the health sector. For this situations, various disciplines have had different studies to minimize the effects of the epidemic. In such cases, it is a separate requirement that the use of the opportunities brought by technology. In this study, the kinematic analysis of the open-source robot arm was especially examined in terms of reducing the workload of individuals working in the healthcare sector. The open-source robot arm is articulated and has 5 degrees of freedom. The kinematic analysis is very important for determination of the working space of the robotic systems. The inverse kinematic analysis was done with Python programming language and the control module was developed to check the analysis. The control module shows the angle values depending on the joints of the robot arm. It is also shown the Px, Py, and Pz positions obtained depending on the position of the end effector in 3D space. On the other hand, Euler angle values are also specified, which are based on the position of the last position taken by the joints of the robot arm in the 3D space. In the study, the geometric approach method was used that is still popular in the inverse kinematic analysis. It is hoped that this study will inspire the development and use of professional and industrial kinds of the open-source robot arm.
Keywords: Open-Source Robot Arm; Inverse Kinematic Analysis; Python